Pengaruh Labelisasi Halal dan Sertifikasi Halal terhadap Minat Beli Produk Makanan dan Minuman UMKM di Kelurahan Mekarwangi Bogor - Supandi, Agus; Widiyarini, Widiyarini; Asikin, Iin; Septariani, Desy; Johan, Ria Susuanti (Jurnal EMT KITA, 2026)
The rapid growth of the food and beverage MSME sector in Indonesia, particularly in areas dominated by Muslim consumers such as Mekarwangi Village in Bogor, highlights the importance of halal assurance in purchasing decisions. This study aims to analyze the influence of halal labeling and halal certification on consumer purchase intention toward food and beverage MSME products. A quantitative approach was employed by distributing questionnaires to 100 respondents. The data were analyzed using multiple linear regression with the assistance of EViews 12 software. The findings reveal that halal labeling has a positive and significant effect on purchase intention, indicating that a clear halal logo on the product packaging can increase consumer confidence in purchasing decisions. Halal certification also has a positive and significant effect and becomes the most dominant factor influencing consumer purchase intention. The regression model explains 91.81% of the variation in purchase intention, while the remaining percentage is explained by other external factors. Classical assumption tests confirm that the model fulfills BLUE criteria, ensuring the validity of the estimation results. This study emphasizes that halal-based marketing strategies are crucial to enhance consumer trust and strengthen the competitive advantage of MSMEs operating in the food and beverage industry within local markets.